An inquiry into privatisation’s impact on healthcare services in Malaysia / Latifa Bibi Binti Musafar Hameed - Musafar Hameed, Latifa Bibi (2014)

(untitled)
Malaysia has experienced significant improvements in the delivery of healthcare services since independence. The Malaysian healthcare system has transformed into a resilient dual-tiered parallel system, with a sizable and booming private sector. The unprecedented growth of the private medical sector has had wide ranging implications for the Malaysian health care system. This thesis seeks to examine the consequences of privatisation on the delivery of healthcare services in Malaysia by following the analytical themes associated with the process. The first analytical theme addresses the consequences of the policy on healthcare expenditure borne by the public and private sectors. The second analytical theme evaluates the consequences of the policy on the distribution of hospitals, beds, doctors (trained/ specialists) and nurses in the country by the public and private sectors. The third analytical theme assesses the consequences of the policy on the distribution of hospitals, beds and doctors by higher and lower level of urbanised states. The evidence shows a trend shift of healthcare expenditure towards the private healthcare sector. Also, contrary to the claims over efforts to ameliorate the burgeoning expense borne by the government, policy has aggressively promoted preferred private operators through medical tourism, grants and concessions. The implicit subsidies have remained but are shared by the private owners. The evidence also shows that public hospitals still have most of the beds and treat patients who cannot afford private care, though medical specialists and experienced nurses have increasingly moved to the private sector. Although the government has iv gradually solved the problem of numbers with regards to doctors by raising the number of approved medical colleges from 1 in1980 to 36 in 2012, there are now serious concerns over the quality of doctors produced by the new colleges. Finally, the evidence also shows that there is a strong urban bias in the privatisation policy. Private hospitals driven by markets are also located in the more urbanised states of Selangor, Penang Johor and the Federal Territory of Kuala Lumpur than the less urbanized states such as Sabah, Sarawak, Pahang and Kelantan, thereby causing an unequal distribution of healthcare. Although the trend bed to doctor ratio and population to doctor ratio between the higher level of urbanization states and lower level of urbanization states shows convergence, the distribution of hospitals, beds and doctors between those states is still unequal. Most of the trained doctors are concentrated in the more urbanized states, while fresh graduates dominated the doctors in the less urbanized states. Hence, we recommend strongly that the government reviews its healthcare policy so that the distribution of resources (hospitals, beds, doctors (including specialists) and nurses) is targeted at serving patients rather than profits.